2019
DOI: 10.1371/journal.pone.0216043
|View full text |Cite
|
Sign up to set email alerts
|

BRAF immunohistochemistry predicts sentinel lymph node involvement in intermediate thickness melanomas

Abstract: Background Sentinel node biopsy (SNB) is an important step in melanoma staging and prognostication. It is commonly performed for patients with intermediate thickness melanomas, based on clinicopathological features. However, only 20–25% of patients eventually demonstrate nodal involvement. The aim of this study was to evaluate whether tissue biomarkers with links to melanoma biology, together with clinicopathological parameters, could aid in the prediction of sentinel node involvement and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
4
1
1
Order By: Relevance
“…A case-control study of Manninen et al enrolled 140 intermediate-thickness melanoma patients with or without SLN involvement, matched for age, gender, Breslow thickness, and location. They tested the common clinicopathological parameters (ulceration, mitotic count, and tumor regression), BRAF immunoreactivity, and cell motility involving actin-modulating proteins, in relation to SLN involvement and survival [28]. They found a significant correlation between SLN status and BRAF mutation; however, our study did not confirm their findings.…”
Section: Discussioncontrasting
confidence: 86%
“…A case-control study of Manninen et al enrolled 140 intermediate-thickness melanoma patients with or without SLN involvement, matched for age, gender, Breslow thickness, and location. They tested the common clinicopathological parameters (ulceration, mitotic count, and tumor regression), BRAF immunoreactivity, and cell motility involving actin-modulating proteins, in relation to SLN involvement and survival [28]. They found a significant correlation between SLN status and BRAF mutation; however, our study did not confirm their findings.…”
Section: Discussioncontrasting
confidence: 86%
“…In this research, we drove several scripts as a bioinformatic visualization and calculation of the clinical samples and tissue optical feature as it had been linked to FMNLs in BrCa access to online databases which contains large cohort and high credibility, evaluating the prognostic value of FMNL expression level in the treatment strategies of breast cancer [ 10 ]. Overall, our research preliminarily but systematically characterized the expression profiles of FMNLs in BrCa and revealed that the detection of the FMNL expression status of BrC patients may be valuable and potential biomarkers for prognostic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Younger age, mitotic rate, and the level of tumour-infiltrating lymphocytes may also influence SLN status [13,14]. BRAF mutations may be correlated with SLN positivity [15]. Expression analysis of isolated markers or of marker combinations may also contribute to predicting lymphatic metastases [16e18] and in addition may identify those patients that will relapse in spite of a negative SN biopsy and therefore can be identified as candidate for adjuvant therapy [19].…”
Section: Introductionmentioning
confidence: 99%